Istikhdām Mawqi‘ Alef Education fī Ta‘līm Mahārah al-Istimā‘ bi al-Madrasah al-Thānawiyyah al-Islāmiyyah al-Ḥukūmiyyah Al-Thāniyah Bukittinggi - Nurul Izzati,; Yelfi Dewi S,; Albaihaqi Anas, (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2026)
This research aims to explore the process of teaching listening skills using Alef Education, identify difficulties in its use, and understand the opinions of teachers and students regarding this media. The researcher employed a qualitative descriptive method and collected data through observation, interviews, and documentation. Non-participant observation was conducted in the eleventh-grade classes (A1 and A2), along with semi-structured interviews with one teacher and twenty students selected using purposive sampling. The results showed that the teaching process begins with a preparatory stage, which includes three activities: preliminary, main, and closing activities. The teacher’s main difficulty was unstable internet connection, while students faced both technical and non-technical challenges. The teacher considered the media very helpful and worth continuing. Students’ opinions were divided into positive and negative; positive responses highlighted the media’s benefits and motivation, while negative responses involved difficulties with independent learning and technical problems.